Observations on the nucleation of ice VII in compressed water - Stafford, S; Chapman, D; Bland, S; Eakins, D (AIP Publishing, 2017)
Water can freeze upon multiple shock compression, but the window material determines the pressure of the phase transition. Several plate impact experiments were conducted with liquid targets on a single-stage gas gun, diagnosed simultaneously using photonic doppler velocimetry (PDV) and high speed imaging through the water. The experiments investigated why silica windows instigate freezing above 2.5 GPa whilst sapphire windows do not until 7 GPa. We find that the nucleation of ice occurs on the surfaces of windows and can be affected by the surface coating suggesting the surface energy of fused silica, likely due to hydroxyl groups, encourages nucleation of ice VII crystallites. Aluminium coatings prevent nucleation and sapphire surfaces do not nucleate until approximately 6.5 GPa. This is believed to be the threshold pressure for the homogeneous nucleation of water.